Observational evidences on the influences of tropical lower atmospheric ∼20 day oscillation on the ionospheric equatorial electrojet - Ramkumar, T.K.; Bhavanikumar, Y.; Rao, D. Narayana; Gurubaran, S.; Babu, A. Narendra; Ghosh, A.K.; Rajaram, R. (My University, 2006)
As an observational evidence, it is reported that long period oscillations near 21- and 30-days generated in the lower atmosphere (troposphere and lower stratosphere) in the Indian tropical regions have possible influences on the lower E region ionospheric currents (say equatorial electrojet [EEJ]) at these periodicities. Dynamical parameters like atmospheric wind velocities are measured in the lower atmosphere (4–20 km) and mesosphere (80–98 km) using the Indian MST radar located at Gadanki (a tropical station) and the MF radar located at Tirunelveli (Indian magnetic equatorial station), respectively, during the time interval of 18 January to 23 April 1999. Using Nd-Yag Rayleigh scatter lidar collocated at Gadanki, the atmospheric temperature profiles are measured in the intermediate height range of 25–80 km for the same period of observation. As a lower E region ionospheric parameter, the EEJ current strengths are measured by determining the geomagnetic field strengths at the Indian EEJ and off-EEJ stations of Trivandrum and Alibag, respectively. Analyses of the data by using fast Fourier transform (FFT), wavelet transform (Morlet wavelet), maximum entropy method (MEM) and Lomb–Scargle periodogram analysis have indicated that it may be possible for the long period oscillations generated in the lower atmosphere to have influences on the E region ionosphere. Possible influences of the solar high energy radiations and magnetospheric origin on EEJ current systems in the periodicity range of ∼20–30 days are also discussed with illustrations.
Keywords: Slow Kelvin waves; Vertical coupling; Equatorial electrojet; Solar influences; EEJ; Kelvin waves